The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.1055/a-0650-4562
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for conversion to snare resection during colorectal endoscopic submucosal dissection in an expert Western center

Abstract: During ESD, the presence of poor lifting, LST-NG morphology, and a difficult retroflexed approach were factors associated with the need to convert to rescue EMR. Conversion to rescue EMR remains a valuable strategy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 35 publications
2
7
0
Order By: Relevance
“…Our study showed LSTs localized mostly in the right colon, similar to those of previous studies in different countries [12][13][14][15][16][17]. LST-G-M was the most common subtype, which contradicted the data from Western countries [3].…”
Section: Discussionsupporting
confidence: 65%
“…Our study showed LSTs localized mostly in the right colon, similar to those of previous studies in different countries [12][13][14][15][16][17]. LST-G-M was the most common subtype, which contradicted the data from Western countries [3].…”
Section: Discussionsupporting
confidence: 65%
“…14,15 Thus, referral of these patients to a center with adequate competence in advanced resection, including ESD, should be recommended. 24,25 The very low NNT of 5 for SMIC when resecting large rectal GM-LSTs well compensates the additional risk of adverse events when replacing piecemeal EMR with ESD. On the other extreme of the spectrum, nonrectal GM-LSTs that are smaller than 4 cm present with a risk of covert SMIC that approximates 5%.…”
Section: Discussionmentioning
confidence: 99%
“…An endoscopist who had 7 years of experience with CR-ESD performed the CR-ESDs. This study described an overall en bloc resection rate of 89.5%, with 81.4% of resections performed only with a knife and 8.1% of resections involving use of a snare [14]. This study illustrates the reality of performing CR-ESD in a Western setting.…”
Section: Discussionmentioning
confidence: 72%